Global optimization of mixed integer signomial fractional programing problems - Jaleh Shirin Nejad; Mansour Saraj; Sara Shokrolahi Yancheshmeh; Fatemeh Kiany Harchegani (Measurement + Control, 2024)
The main issue in the present article is to investigate how to solve a mixed integer fractional signomial geometric programing problem (MIFSGP). In the first step to achieving this idea, we must convert a fractional signomial programing problem into a non-fractional problem via a simple conversion technique. Then, a convex relaxation with a new modified piecewise linear approximation with integer break points as a pre-solve method is used to reach an integer global optimum solution. A few numerical examples are included to illustrate the advantages of the proposed method